1986
DOI: 10.3354/meps029007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Spartina detritus enrichment on exchange of nutrients between sediment and water in an intertidal area of Bay of Fundy

Abstract: The influence of Spartina alterniflora detritus on exchange of nitrate + nitrite, ammonia, and phosphate between sediment and water was studied after burial of plant litter in a muddy intertidal sediment in Cobequid Bay, Bay of Fundy. The enriched area in general showed higher flux rates than the control area. Dissolved inorganic nitrogen (DIN) flux was dominated by ammonium. Ammonium was normally only released from the sediment and maximum release rates were 300 and 180 pm01 NH:-N m-2 h-' in the enriched and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
(22 reference statements)
2
7
0
Order By: Relevance
“…Both bioturbated and control sediments seemed to retain [ 14C]DOC equally well. Andersen and Hargrave (1984) found a similar low release of DOC from plant material buried in intertidal sediments, although a 14% loss of C as DOC occurred during a 6-d laboratory leaching experiment without sediment. Kepkay and Andersen (198 5) found that most of the DOC produced from 14C-labeled detritus actually was mineralized in the sediment and released to overlying water as 14C0…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Both bioturbated and control sediments seemed to retain [ 14C]DOC equally well. Andersen and Hargrave (1984) found a similar low release of DOC from plant material buried in intertidal sediments, although a 14% loss of C as DOC occurred during a 6-d laboratory leaching experiment without sediment. Kepkay and Andersen (198 5) found that most of the DOC produced from 14C-labeled detritus actually was mineralized in the sediment and released to overlying water as 14C0…”
Section: Discussionmentioning
confidence: 88%
“…3) Aller 1978;Henriksen et al 1980Henriksen et al , 1983Kristensen 1984Kristensen , 1985Andersen and Kristensen 1988). The influence of ventilation on pore-water alkalinity is clearly evident, with much lower concentrations measured in deeper layers of bioturbated sediment than in defaunated controls (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Other studies show different dynamics (Hackney & de la Cruz, 1980 ;Buth & Wolf, 1985 ;Andersen, 1986) and interpretations are difficult .…”
Section: Discussionmentioning
confidence: 99%